(untitled) (Research, Society and Development, 2020)
Objective: to understand the applicability and contributions of the main hospital indicators are addressed in the literature. Method: this is an integrative literature review, with the databases searched SciElo, Lilacs and PubMed, the inclusion criteria were publications from the last five years in Portuguese and English, in addition a validated and adapted instrument was used for the study. Results: of the 18 articles analyzed, they found that in relation to the year of publication, there were two (11.11%) in 2015, one (5.56%) in 2017, three (16.67%) in 2018, eleven (61.11%) in 2019 and one (5.56%) in 2020, regarding the type of institution, one (5.56%) in private hospitals, thirteen (72.22%) in public hospitals and four (22.22%) do not apply. Final Considerations: it was evidenced that the indicators were applied to assess hospitalization rate, length of stay, mortality rate and quality and performance assessment through hospital indicators, in addition, it was possible to verify that in some countries they have realities similar to that of the Brazil even if they have different health systems.